The Wisdom of Thoth Magical Texts in Ancient Mediterranean Civilisations. - Bąkowska-Czerner, Grażyna (Archaeopress, 2016)
This volume represents a selection of contributions on Mediterranean themes from a wider international interdisciplinary conference on Magical Texts in Ancient Civilizations, organised by the Centre for Comparative Studies of Civilizations at Jagiellonian University in Kraków in Poland between 27-28 June 2013.